2014 6th International Conference on Electronic Voting: Verifying the Vote (EVOTE) 2014
DOI: 10.1109/evote.2014.7001142
|View full text |Cite
|
Sign up to set email alerts
|

Electronic voting with fully distributed trust and maximized flexibility regarding ballot design

Abstract: One common way to ensure the security in voting schemes, is to distribute critical tasks between different entities-the so called trustees. While in most election settings, election authorities perform the task of trustees, elections in small groups such as board elections can be implemented in a way that all voters are also trustees. This is actually the ideal case for an election as trust is fully distributed. A number of voting schemes have been proposed for such elections. Our focus is on a mix net based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Further methods to improve cast-as-intended verifiability in Helios-like protocols have been proposed in the Selene protocol [31], which introduced tracking number appended to the cast votes, and Guasch et al [32], [33] employing designated-verifier proofs. For boardroom voting, an Android application extending and implementing the protocol behind Helios was developed [34]. From the usability perspective, a number of suggestions for the improvements of the current Helios implementation that simplify the audit process for the voters, have been proposed [35], [36].…”
Section: A Helios Extensionsmentioning
confidence: 99%
“…Further methods to improve cast-as-intended verifiability in Helios-like protocols have been proposed in the Selene protocol [31], which introduced tracking number appended to the cast votes, and Guasch et al [32], [33] employing designated-verifier proofs. For boardroom voting, an Android application extending and implementing the protocol behind Helios was developed [34]. From the usability perspective, a number of suggestions for the improvements of the current Helios implementation that simplify the audit process for the voters, have been proposed [35], [36].…”
Section: A Helios Extensionsmentioning
confidence: 99%
“…Ritter [10] adapted the technique of homomorphic tallying to the boardroom voting context and proposed two derivations of his protocol tailored towards simple and complex ballots. In similar vein, Kulyk et al [11] adapted the technique of reencryption mix net-based election to the boardroom voting context. Further, Khader et al [12] suggested a boardroom voting protocol building upon self-dissolving commitments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We do not take into account the computational complexity of the generation of general public parameters, such as the group used in the calculations or the independent generators of that group. We decided to limit our analysis to the theoretical performance only: while there have been practical implementations of the considered protocols [10,11,14,15], a performance comparison between them is infeasible due to difference in the implementations, such as software architecture, ways of network communication etc. Finally, we provide a performance comparison of all considered protocols within different election settings.…”
Section: Tallyingmentioning
confidence: 99%
See 2 more Smart Citations